The Relationship Between Emotional Intelligence and the Modern Methods of Second Language Teaching - Mariwan Asaad Bahaaldin; Abdullah Hussein Rasool (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Current researches point to the importance of emotional intelligence and the impact of its consequences on teachers’ performance and students’ success in second language learning. This study aims to understand the importance of the role of emotional intelligence (EI) and its relation to the most effective teaching method in second language teaching by using the domains of emotional intelligence, which help one's ability to recognize and understand his/her emotions، as well as understanding the emotions of others around them and empathize with them. Negative emotions such as stress,anxiety، and fear of doing mistakes, in which they are the main obstacles in learning a second language Controlling and converting these emotions into positive motivations for achieving the goal is due to high-level emotional intelligence. This is achieved through creating a peaceful and appropriate environment of personal and social relationships in the classroom، which enhances the student's verbal competence and ultimately gives him the strength of self-confidence and continuity. The research focuses on two areas: First, the introduction of the concept of emotional intelligence and models of emotional intelligence such as Goelman، BarOn، and Mayer and Salovey mentioned. The second area is the new methods of teaching English، which are produced under the influence of positive psychology. The most important of these are Advanced Methods Company (AMCO)، Content and Language Integrated Learning (CLIL), Direct method, Communicative Language teaching (CLT) and Task-Based Learning. As a result، it turned out that all of the methods described were indirectly related to emotional intelligence، but the Advanced Methods Company (AMCO) was based on the theory of multi-intelligence، which considers each student's psychological amount based on competence.